2010
DOI: 10.1371/journal.pone.0008780
|View full text |Cite
|
Sign up to set email alerts
|

GABA Increases Electrical Excitability in a Subset of Human Unmyelinated Peripheral Axons

Abstract: BackgroundA proportion of small diameter primary sensory neurones innervating human skin are chemosensitive. They respond in a receptor dependent manner to chemical mediators of inflammation as well as naturally occurring algogens, thermogens and pruritogens. The neurotransmitter GABA is interesting in this respect because in animal models of neuropathic pain GABA pre-synaptically regulates nociceptive input to the spinal cord. However, the effect of GABA on human peripheral unmyelinated axons has not been est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…) and humans (Carr et al. ); however, activation of peripheral GABA A receptors elicits neither spontaneous pain behavior nor mechanical sensitivity in naïve animals. One proposal to this apparent paradox is the phenomenon of primary afferent depolarization (Rudomin and Schmidt ; Willis ) whereby sub‐threshold depolarization results in inactivation of voltage‐gated channels.…”
Section: Discussionmentioning
confidence: 99%
“…) and humans (Carr et al. ); however, activation of peripheral GABA A receptors elicits neither spontaneous pain behavior nor mechanical sensitivity in naïve animals. One proposal to this apparent paradox is the phenomenon of primary afferent depolarization (Rudomin and Schmidt ; Willis ) whereby sub‐threshold depolarization results in inactivation of voltage‐gated channels.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the existing literature on the action of GABA on peripheral sensory neurons, these results are in part controversial. In contrast to the inhibitory profile of GABA in the central nervous system, GABA is known to induce a depolarization and an increased excitability in sensory neurons from frogs (45), cats (46), rats (46 -48), and humans (49). Accordingly, GABA A receptors are expressed in primary afferent neurons with a significant coexpression with nociceptive markers such as TRPV1 (50 -53).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas GABA A receptors appear to be expressed in the majority of DRG neurons, it was suggested that only those neurons expressing the Ca v 3.2/␣1H T-type calcium channel are able to generate GABA-induced action potentials (57). Accordingly, a recent report from Carr et al (49) demonstrated a GABA A receptor-mediated increase in excitability in only ϳ40% of C-fibers in human peripheral nerves. Notably, the same study only reported an increased electrical excitability and not an activation of C-fibers by GABA.…”
Section: Discussionmentioning
confidence: 99%
“…Slight depolarization can increase excitability, depending on the stimulus paradigm used. This is for example true for GABA A -mediated responses in a subset of unmyelinated peripheral axons in humans (Carr et al , 2010). Some hippocampal pyramidal cells fire ectopic axonal spikes during some forms of oscillatory network activity during the phase when proximal compartments are inhibited (Papatheodoropoulos, 2008).…”
Section: Synaptic and Neuromodulatory Effects On Axonsmentioning
confidence: 99%